Nutrition and economic development: Exploring Egypt's exceptionalism and the role of food subsidies - Ecker, Olivier; Al-Riffai, Perrihan; Breisinger, Clemens; El-Batrawy, Rawia (International Food Policy Research Institute, 2016)
This book’s main hypothesis is that Egypt’s large food subsidy system has been ineffective in reducing undernutrition; in fact, it may have contributed to sustaining and even aggravating both nutrition challenges. For a long time, the subsidy system provided only calorie-rich foods, at very low and constant prices and with quotas much above dietary recommendations. This system has created incentives to consume calorie-overladen and unbalanced diets, increasing the risks of child and maternal overnutrition and, at high subsidy levels, the risk of inadequate child nutrition. Moreover, the large public budget allocated to the food subsidies is unavailable for possibly more nutrition-beneficial spending, such as for child and maternal nutrition-specific interventions. The authors’ findings consistently suggest that—in addition to the well-known economic rationale for reforming the Egyptian food subsidy system—there are strong reasons to reform food subsidies due to nutrition and public health concerns. A fundamental food subsidy reform process has been under way since June 2014. The already-implemented changes can be expected to have reduced some incentives for overconsumption and may have positive dietary effects. However, further major reform efforts are needed to transform the current subsidy system into a key policy instrument in the fight against malnutrition. The findings of this book should be valuable to policy makers, analysts, development partners, and others concerned with improving food security and promoting healthy nutrition in Egypt and other developing countries with large social protection programs.